A cardiac arrest on a spiked helmet electrocardiographic sign in anterior leads in a patient with a diagnosis of acute myocardial infarction: A case report. (May 2022) - Belarbi, Zakariae; Brem, Falmata Laouan; El Ouafi, Noha
Abstract: In patients with critical heart disease, such as acute coronary syndrome, aortic dissection, and other diseases, ST-segment elevation is a relatively common finding on the electrocardiogram (ECG). There are various other well-known signs described in heart diseases, such as negative T waves and q waves of necrosis. The "spiked helmet sign" is a novel electrocardiographic sign described first in 2011, whose pathophysiology and clinical applicability remain uncertain at this time. Herein we report the case of a cardiac arrest in a patient who developed the "spiked helmet electrocardiographic sign" concomitantly with acute myocardial infarction, leading to the patient's death from ventricular fibrillation. This case report aims to discuss the "spiked helmet electrocardiographic sign", and to detail the prognostic and diagnostic interest of this sign, wich seems to be different from a standard ST segment elevation. Highlights: Cardiovascular diseases are the world's first and foremost cause of death. The "spiked helmet sign" is a rare electrocardiographic sign recently described in 2011 that can be found in a variety of serious diseases, the most common is the acute coronary syndrome. This sign is described as a potential novel ECG marker of a very high risk of impending death. This sign may be used in the future to detect critically ill patients, in order to speed up treatment strategies. Clinicians must be vigilant in front of such a sign.